Sabbath-keeping in the Bible from the perspective of biblical spirituality - De Villiers, Pieter G. R. (HTS teologiese studies, 2021)
This article responds to the renewed interest in the spiritual practice of Sabbath-keeping by investigating its nature and meaning in the Judeo-Christian traditions. After briefly analysing the reasons for the contemporary neglect of Sabbath-keeping and indications of its renaissance, this article will analyse biblical pronouncements about the Sabbath, mainly from Hebrew Scriptures, but with brief attention to Christian Scriptures that provide various insights of decisive importance to understand and explain its prominent place for faith communities, but that are vitally important for reinvigorating Sabbath-keeping in a contemporary context. It analyses pronouncements in the Bible in Genesis 2:1–3 that highlights the Sabbath as joyful resting; the need for Sabbath-keeping as commandment in Exodus 20:9–11 and in Deuteronomy 5:12–15, and, finally Sabbath-keeping as trust in God as the provider in Exodus 16:1–30. Various spiritual insights and implications of these passages will be discussed. The article assumes historical critical insights as developed in biblical studies but develops a theological analysis that explains the spiritual dynamics in these texts. These spiritual insights explain the prominence of Sabbath-keeping in the Bible and its practice in the Judeo-Christian religious discourse.Contribution: This article contributes to scholarship on spiritual practices, by analysing the nature and meaning of Sabbath-keeping in Genesis 2:1–3, Exodus 20:9–11; Deuteronomy 5:12–15 and Exodus 16:1–30, stressing their spiritual dynamics in terms of joyful resting, as commandment, as trust in divine provision and as a reflection of their covenantal nature.